1803 Does Volume of the Mask Vary and Influence Measurements During Neonatal Resuscitation?. (October 2012) - Vonderen, JJ van; Kamar, R; Schilleman, K; Hooper, SB; Walther, FJ; Pas, AB te
Abstract : Background: Respiratory function monitoring (RFM) could improve the efficiency of mask ventilation in preterm infants at birth. However, dead space of a mask could vary, depending on rate of pressurization and variation in hand hold, influencing measurements. Aim: To investigate whether mask volume varies during mask ventilation and influences measured tidal volumes and calculated mask leak. Methods: Thirty caregivers of the neonatal unit were asked to mask-ventilate a leak free manikin with pressures 25/5 cm H2 O and a gas flow rate of 6 and 10 L/min. A Laerdal 0/1 mask (40 mL) was glued leak free on the face in the right position but the participant was unaware why the mask position was fixed. The participant was told that mask hold, not positioning, was tested and that it was still possible to have leak. Tidal volumes were measured using a RFM. Results: Inspired tidal volume (VTi ) increased from 8.05 mL (0.76) at 6 L/min to 8.76 mL (0.75) at 10 L/min (p<0.01) and expired tidal volume (VTe ) from 8.15 mL (0.81)) at 6 L/min to 8.85 mL (0.75) at 10 L/min (p<0.001). Median (IQR) leak was –0.90 (–3.90–1.40) % with 6 L/min and did not increase with 10 L/min (–0.62 (–3.43–1.80) %; ns) Coefficient of variance showed good to acceptable agreement for all results. Conclusion: During mask ventilation there is very little variation in mask volume which does not influence respiratory function monitoring.